Two-Mode Operation Engine Mount Design for Automotive Applications. (2012) - Tikani, Reza; Vahdati, Nader; Ziaei-Rad, Saeed
Abstract : Hydraulic engine mounts are applied to the automotive applications to isolate the chassis from the high frequency noise and vibration generated by the engine as well as to limit the engine shake motions resulting at low frequencies. In this paper, a new hydraulic engine mount with a controllable inertia track profile is proposed and its dynamic behavior is investigated. The profile of the inertia track is varied by applying a controlled force to a cylindrical rubber disk, placed in the inertia track. This design provides a hydraulic engine mount design with an adjustable notch frequency location and also damping characteristics in shake motions. By using a simple control strategy, the efficiency of the proposed hydraulic engine mount in two-mode operation meaning isolating mode in the highway driving condition and damping mode in the shock motions, is investigated.